1995
DOI: 10.1063/1.469620
|View full text |Cite
|
Sign up to set email alerts
|

Electronic absorption spectra of linear carbon chains in neon matrices. I. C−6, C6, and C6H

Abstract: Electronic absorption spectra of linear C−6, C6, and C6H have been identified in neon matrices at 5 K. The species were produced by codepositing mass selected cations and anions with neon. The ions were generated in a hot cathode discharge source using diacetylene. The spectra of C−6 and C6 could also be observed using a pure carbon anion source or laser vaporization of graphite. The assignment is based on the mass selection, experimental and spectroscopic evidence, leading to the location of the 000 transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 33 publications
2
95
0
Order By: Relevance
“…The C 2 peaks (synthetic spectrum shown in bottom trace) were subtracted after fitting by a Voigt line shape (of variable width and amplitude and baseline). The band is blue-shifted by 99 cm Ϫ1 from the neon matrix value, similar to the 142 cm Ϫ1 change observed for the C 6 H 2 ⌸ Ϫ 2 ⌸ electronic transition [11,12]. Both systems have similar characteristics involving 2 4 3 3 Ϫ 2 3 3 4 for C 6 H and 2 4 12 2 3 2 Ϫ 2 3 12 2 3 3 orbital configuration for C 6 H ϩ with the same electron being excited.…”
Section: Observationssupporting
confidence: 56%
See 1 more Smart Citation
“…The C 2 peaks (synthetic spectrum shown in bottom trace) were subtracted after fitting by a Voigt line shape (of variable width and amplitude and baseline). The band is blue-shifted by 99 cm Ϫ1 from the neon matrix value, similar to the 142 cm Ϫ1 change observed for the C 6 H 2 ⌸ Ϫ 2 ⌸ electronic transition [11,12]. Both systems have similar characteristics involving 2 4 3 3 Ϫ 2 3 3 4 for C 6 H and 2 4 12 2 3 2 Ϫ 2 3 12 2 3 3 orbital configuration for C 6 H ϩ with the same electron being excited.…”
Section: Observationssupporting
confidence: 56%
“…It should be noted that the presence of the three R-band heads (at the higher energy end) readily differentiates this from absorptions belonging to a band within the 2 ⌸ Ϫ 2 ⌸ system of C 6 H, which are seen throughout this wavelength region [12]. Furthermore, the assignment to a band within the 3 ⌺ Ϫ Ϫ X 3 ⌺ Ϫ transition of C 6 , with observed origin at 19558 cm Ϫ1 in a neon matrix [11] is excluded as the rotational spacing would be roughly twice as large as between the lines for C 6 H ϩ because of nuclear spin statistics.…”
Section: Observationsmentioning
confidence: 99%
“…In Table II, the vertical excitation energies calculated in the present paper are compared with the experimental values. The papers of Maier and co-workers [12][13][14][15][16] provide low vertical energies for the lowest states. Generally, our MRCI vertical excitation energies agree relatively well with the experimental T 0 determinations of Refs.…”
Section: On the Electronic Excited States Of Cmentioning
confidence: 99%
“…For r-C 4 , Mühlhäuser et al 11 have located several singlet states in the 0 -5 eV internal energy range. Experimentally, numerous accurate data on these electronic states have been published by Maier and co-workers [12][13][14][15][16] and Jungen and Xu 17 using photoelectron spectroscopy and by the absorption spectra of C 4 in cold matrices. Xu et al 18 reported vertical excitation energies for l-C 4 from photoelectron spectroscopy and ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic transitions in carbon clusters have been proposed as possible candidates for the diffuse interstellar bands. 3,4,17,18 This has motivated Maier and co-workers [19][20][21][22] to study the ultraviolet (UV) and visible absorption spectroscopy of mass-selected carbon clusters deposited in a cryogenic matrix, obtaining vibrationally resolved electronic transitions for C 4 , C 5 , and C 6 . Further information on excited electronic states comes from anion photoelectron spectroscopy, [14][15][16] which reveals states that are optically inaccessible from the neutral ground state, and electronic structure calculations.…”
Section: Introductionmentioning
confidence: 99%